Do ambiguous images provide psychological insights? Testing a popular claim - Richard Wiseman; Caroline Watt (PeerJ)
Social media posts and websites claim that the way in which people perceive ambiguous images reveals insights into their personality and thinking style. To explore this notion, participants indicated the first image that they perceived in four ambiguous pictures (Duck-Rabbit, Younger-Older Woman, Rubin’s Vase and Horse-Seal), and completed a Five Factor personality measure along with scales relating to optimism, procrastination, holistic thinking, and decision-making style. Many of the claims received no empirical support and so constitute a new type of psychological myth. Future research could explore why these claims remain popular with the public and why people frequently share the material with others. In addition, several significant and interesting findings emerged, including associations between Duck-Rabbit, personality, and optimism, and Younger-Older Woman and age. Possible future research into these phenomena is discussed.